The effects of a 6-week controlled, hypocaloric ketogenic diet, with and without exogenous ketone salts, on cognitive performance and mood states in overweight and obese adults - Kackley, Madison L.; Brownlow, Milene L.; Buga, Alex; Crabtree, Chris D.; Sapper, Teryn N.; O’Connor, Annalouise; Volek, Jeff S. (Frontiers in Neuroscience, 2022)
Background: Strategies that elevate circulating ketones are increasingly associated with improved neurocognitive function during stress or in individuals with neurological disorders, but little is known how ketones influence cognition and mood during weight loss in lieu of different sodium levels. Objectives: To investigate the effects of an exogenous ketone salt (KS) as part of a hypocaloric KD on mood and cognitive outcomes in overweight and obese adults. A secondary objective was to evaluate changes in biochemical markers associated with inflammatory and cognitive responses. Methods: Adults with overweight and obesity participated in a 6-week controlled-feeding intervention comparing hypocaloric diets (~75% of energy expenditure). KD groups received twice daily ketone salt (KD+KS; n = 12) or a flavor-matched placebo, free of minerals (KD+PL; n = 13). A separate group of age and BMI matched adults were later assigned to an isoenergetic low-fat diet (LFD; n = 12) as comparison to KD. Mood was assessed by shortened Profile of Mood States and Visual Analog Mood Scale surveys. Cognitive function was determined by the Automated Neuropsychological Assessment Metrics mental test battery. Results: Both KD groups achieved nutritional ketosis. Fasting serum glucose decreased in both KD groups, whereas glucose was unaffected in the LFD. Insulin decreased at week 2 and remained lower in all groups. At week 2, depression scores in the KD+PL group were higher compared to KD+KS and happiness showed nonsignificant higher scores in KD+KS group compared to both KD+PL and LFD. Performance in the math processing and go/no-go cognitive tests were lower for KD+PL and LFD participants, respectively, compared to KD+KS. Serum leptin levels decreased for all groups throughout the study but were higher for KD+KS group at week 6. Serum TNF-α steadily increased for LFD participants, reaching significance at week 6. Conclusion: During a short-term hypocaloric diet, no indication of a consistent decline in mood or cognitive function were seen in participants following either KD, despite KD+PL being relatively low in sodium. WK2 scores of ‘anger’ and ‘depression’ were higher in the LFD and KD+PL groups, suggesting that KS may attenuate negative mood parameters during the early intervention stages.